TYPES OF INNOVATION AND ANALYSIS OF THEIR USAGE IN ECONOMY OF UZBEKISTAN - Nigora A. Ashurmetova (Plekhanov Russian University of Economics, 2019)
The article shows different types of innovation and analyzes the number of technological, organizational and marketing innovation introduced in the Republic of Uzbekistan. When costs of innovation were analyzed it was found out that the principle source of financing innovation enterprises was the country’s own funds, which in 2017 made 2 956.0 bn sums or 71%. The structure of the processing industry was also studied by the degree of technological types of production, where the major share falls on low-technological types of production. Taking into account the importance of highly-technological types of production the necessity of their extension was grounded. Innovation by types of activity was studied, specific features of innovation processes in agriculture were identified and key problems connected with the usage of different types of innovation was summarized and it can bring us to the conclusion that classification of innovation by different criteria can help build the structure and use efficient methods of management corresponding to each type of innovation. The proposed lines in innovation policy could create conditions necessary to intensify innovation processes in different industries and sectors of national economy of Uzbekistan. The research was based on the complex approach to the subject being investigated and used analytical, graphic and monographic methods as well as the logical analysis.